KAJIAN KETAHANAN PANGAN DAN KERAWANAN PANGAN DI PROVINSI BENGKULU - Mulyasari, Gita (Jurnal AGRISEP, 2016)
Bengkulu Province develop Food Security and Vulnerability Atlas (FSVA) which is a very significant tool in planning and decision making to reduce the gap of food security in Bengkulu Province.  This research was conducted in Bengkulu Province using descriptive methods.  The data used is secondary data collected from literature relating to food security and food insecurity in Bengkulu Province. FSVA can detect food security and food insecurity conditions is based on 9 indicators, a) normative consumption ratio, b) The percentage of population under the poverty line, c) the number of villages with no public transportation access, d) the percentage of households without electricity access, e) life expectation, f) illiterated women, g) under height toddlers, h) households without clean water access, and the last i) the percentage households far from healthy access.